2007
DOI: 10.1364/ol.32.002726
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fluorescence bioimaging with an all-semiconductor laser picosecond pulse source

Abstract: We have demonstrated successful two-photon excitation fluorescence bioimaging using a high-power pulsed all-semiconductor laser. Toward this purpose, we developed a pulsed light source consisting of a mode-locked laser diode and a two-stage diode laser amplifier. This pulsed light source provided optical pulses of 5 ps duration and having a maximum peak power of over 100 W at a wavelength of 800 nm and a repetition frequency of 500 MHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 0 publications
0
52
0
Order By: Relevance
“…Another trend towards practical TPM system is the development of compact and turn-key light sources. The emerging compact laser systems are based on semiconductor laser-diode (LD) systems [15,27,[51][52][53]59,60] , optical fiber laser systems [57,58,61] , and even chip-size devices [62] . LD has been used as a reliable, low-cost, highperformance light source in scientific research, optical communication, andinformation technologies.…”
Section: Laser Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Another trend towards practical TPM system is the development of compact and turn-key light sources. The emerging compact laser systems are based on semiconductor laser-diode (LD) systems [15,27,[51][52][53]59,60] , optical fiber laser systems [57,58,61] , and even chip-size devices [62] . LD has been used as a reliable, low-cost, highperformance light source in scientific research, optical communication, andinformation technologies.…”
Section: Laser Systemmentioning
confidence: 99%
“…Photo of 500-MHz repetition rate, 2.7-ps pulse width, and 1-µm semiconductor laser oscillator [15] . (c) TPM of convoluted tubules in mouse kidney tissues stained with Alexa Fluor 488 using all-semiconductor light source [53] . (d) TPM of brain Purkinje cells express GFP using 1 030-nm semiconductor light source [15] .…”
Section: Laser Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that pulse durations as short as a few picoseconds are required in order to get two photon excitation and second harmonic generation images from biological samples [5][6]. Picosecond pulses can be also used as a seed source for a master oscillator power amplifier (MOPA) for industrial applications like micro-machining and ablation [11].…”
Section: Laser Characteristics Without Sweepingmentioning
confidence: 99%
“…One possible weak side of picosecond pulses versus femtosecond pulses would be towards other nonlinear microscopy applications like second harmonic generation (SHG) microscopy and two photon excitation (TPE) microscopy. However it has been also demonstrated that a several picoseconds pulse width is efficient enough to get high contrast image in second harmonic generation (SHG) microscopy and two-photon excitation (TPE) microscopy [5][6].…”
Section: Introductionmentioning
confidence: 99%